The effect of home advantage in professional futsal - Soares Leite, W. S. (Trends in Sport Sciences, 2017)
Home advantage is an important factor to consider within the competitive sport and lets you know what effect it has to compete at home or away in the outcome of sporting competitions. Aim of Study. The objective of this study is to analyze the effect of home advantage in professional futsal, making an analysis and comparison between the 10 major national leagues in the world. Material and Methods. In total, 1.439 games were analyzed in 8 national futsal leagues. The results were obtained through the website Resultados and/ /or the websites of respective national federations. To quantify the home advantage, the methodology of percentage points was used. Results. According to the results, only at Italian futsal league did not present positive result, percentage of points gained above 50% in favour of the teams that play at home. The average percentage found in this study for home advantage was 56.15 ± 6.15% of the total accumulated points. Conclusions. We can conclude that to play at home in the main futsal leagues of the world presents advantage for the outcome of the matches